Evaluation of inert tracers in a bedrock fracture using ground penetrating radar and thermal sensors. (May 2017) - Hawkins, Adam J.; Becker, Matthew W.; Tsoflias, Georgios P.
Highlights: Anisotropic heat exchange was observed via a network of thermal sensors. Inert tracer tests in two well-pairs suggested identical fluid volumes. Heat exchange experiments revealed heat transfer differed significantly. Moment analysis of heat transport shows surface area and flow rate dominate. Abstract: The spatial distribution of fracture/matrix heat exchange was measured while hot water was circulated through a single bedding plane fracture in shallow bedrock. The field site is interpreted here as a simple model for a geothermal reservoir. Thermal breakthrough was recorded at the production well and Fiber-Optic Distributed Temperature Sensing (DTS) monitored temperature in the rock matrix. Conservative tracer tests revealed that the reservoir fluid volume in two separate experiments were nearly identical. Thermal breakthrough measurements, however, revealed that reservoir fluid volume did not correlate to thermal performance because the two experiments encountered different effective areas of heat transfer along the fracture. Ground Penetrating Radar imaging of subsurface tracer transport and DTS corroborate these findings.a cold reservoir